2013
DOI: 10.3109/01902148.2013.816803
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy in lung disorders: Pathogenesis of lung diseases and mechanism of action of mesenchymal stem cell

Abstract: Lung disorders such as asthma, acute respiratory distress syndrome (ARDS), chronic obstructive lung disease (COPD), and interstitial lung disease (ILD) show a few common threads of pathogenic mechanisms: inflammation, aberrant immune activity, infection, and fibrosis. Currently no modes of effective treatment are available for ILD or emphysema. Being anti-inflammatory, immunomodulatory, and regenerative in nature, the administration of mesenchymal stem cells (MSCs) has shown the capacity to control immune dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 110 publications
1
51
0
1
Order By: Relevance
“…Given that MSCs generate their therapeutic action through cell engraftment differentiation to directly repair injured tissues or through paracrine to facilitate self-healing of tissues20, we labeled UC-MSCs with DAPI in vitro and then tracked the labeled UC-MSCs in ALI mice post-injection at different times. The results showed that UC-MSCs were concentrated in the trachea 0 h post-injection, continuously infiltrated the lung parenchyma though the tracheal wall 12 h post-injection, and populated the whole lung parenchyma 24 h post-injection.…”
Section: Resultsmentioning
confidence: 99%
“…Given that MSCs generate their therapeutic action through cell engraftment differentiation to directly repair injured tissues or through paracrine to facilitate self-healing of tissues20, we labeled UC-MSCs with DAPI in vitro and then tracked the labeled UC-MSCs in ALI mice post-injection at different times. The results showed that UC-MSCs were concentrated in the trachea 0 h post-injection, continuously infiltrated the lung parenchyma though the tracheal wall 12 h post-injection, and populated the whole lung parenchyma 24 h post-injection.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs are considered to be immunoprivileged because of their low immunogenicity as they express very low levels of MHC class I and no MHC class II and, furthermore, do not induce activation of allogeneic lymphocytes (41,42), which enables allogeneic MSCs to evade the allogeneic immune system and allows for their usage across MHC barriers. Previous studies have shown that MSCs can improve the symptoms of autoimmune diseases, such as ALI, by executing immunomodulatory effects through paracrine mechanisms, reducing systemic inflammation, mitigating tissue damage, and achieving tissue regeneration through colonization and differentiation after migration to the lesion (12,13,43,44). The migration of MSCs in vivo after transplantation is inefficient, which limits their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether as cause or consequence, the acute and chronic lung injury found in these diseases invariably involves aberrant immune activity and fibrosis [109, 110]. MSC therapy, indeed most cell therapies, may be particularly suited for use in pulmonary diseases since it has been consistently shown that the overwhelming majority (usually 80 ~ 90 %) of MSCs delivered intravenously—likely the most clinically feasible method for introduction of cellular products—will rapidly reach the lungs [111].…”
Section: State Of Msc Clinical Research In Specific Immune-/inflammatmentioning
confidence: 99%